GROWTH, PROTEIN EFFICIENCY RATIO AND PROTEIN RETENTION OF G6 TRANSGENIC MUTIARA CATFISH WITH MIXED FEEDING AT DIFFERENT RATIO OF COMMERCIAL FEED AND REBON SHRIMP FLOUR - Ibnu Dwi Buwono; Roffi Grandiosa; Iskandar Iskandar; Vina Rahmawati (Universitas Mataram, 2024)
This study aims to evaluate the growth of transgenic G6 mutiara catfish using a mixture of commercial feed and rebon shrimp meal with different ratios between treatments. This research was carried out in May-August 2023, in the Lab. Aquaculture Gd.4 Faculty of Fisheries and Marine Sciences, Padjadjaran University. This research used the experimental method Completely Randomized Design (CRD) with four treatments and three replications. Treatment in the form of a mixture of commercial feed and rebon shrimp meal with a ratio of 50:50 (A), a ratio of 65:35 (B) and a ratio of 80:20 (C) was given to G6 transgenic mutiara catfish and the control treatment (65:35 ratio) given to sangkuriang catfish (treatment B*). Maintenance was carried out for 56 days with feeding three times a day. The parameters observed included growth in absolute weight (Wg), feed conversion ratio (FCR), protein efficiency ratio (PER), and protein retention (RP) which were analyzed using Analysis of Varience with 95% confidence level if significantly different followed by Duncan's test using SigmaPlot 15.0 software. The research results showed that the addition of commercial feed and rebon shrimp flour with a ratio of (80:20) had an influence on growth performance as indicated by an increase in absolute weight gain (687,53 g), FCR (0,64), protein efficiency ratio (18,7) and protein retention (46,43%.) Water quality values during rearing were still within tolerable limits for the growth of G6 transgenic mutiara catfish.